ANALISIS ISI BERITA PENOLAKAN NENO WARISMAN DI GORIAU.COM - Desiyari Natalia Br. Tambunan; Chelsy Yesicha (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Information that contains conflict value is information with high news value. The press in covering conflict news needs to pay attention to its packaging so it does not get bigger but, instead, it results in conflict resolution. Likewise, the conflict in Pekanbaru related to the rejection of the arrival of Neno Warisman to declare hashtag # 2019GantiPresiden had made a commotion before the 2019 Election. News about the conflict between the pros and cons of this activity, became the main focus for the local Riau media, in particular, GoRiau.com. This research wants to see the packaging of conflict news experienced by Neno Warisman with the concept of peaceful journalism. The concept of peaceful journalism will be seen in line with the theory used, namely, the theory of social responsibility.This research uses a quantitative method with a content analysis approach. The research subject used was the news narration of Neno Warisman's rejection in online media GoRiau.com which was published on 25 to 27 August 2018 in a total of 16 news. This study uses codification (coding) to get the results of research with two coders.Based on the results of the study, news of Neno Warisman's rejection on GoRiau.com applied 53.12% peace orientation, 89.06% truth orientation, 60.94% community orientation and 34.48% problem-solving orientation with a percentage of peace journalism as 57.5%. However, media GoRiau.com needs to pay attention to the application of conflict news conflict orientation solutions, especially for indicators of improvement efforts. Because it was found that this media did not provide information in efforts to remedy the conflict. Regarding social responsibility theory, it was found that media GoRiau.com applied this theory, as seen in the application of news, it presented news in an actual way, informed based on facts, and was transparent in reporting on this conflict. Although, not found a high number to solve the problem.Keywords: Content Analysis, GoRiau.com, News, Neno Warisman’s Rejection, Peace  Journalism